FAMILY AGROMYZIDAE - Sousa, Viviane Rodrigues De; Couri, Márcia Souto (Zootaxa, 2016)
Agromyzidae are a family with many species described throughout the world. The family is known as leaf-miner flies, for the phytophagous habits of their larvae, feeding within plant tissues. This catalogue presents 74 species recorded from Colombia, distributed in 12 genera and two subfamilies. For each species we present the available geographical distribution in the country.